The Role of Aggression-Related Cognition in the Aggressive Behavior of Offenders: A General Aggression Model Perspective. (February 2013) - Gilbert, Flora; Daffern, Michael; Talevski, Diana; Ogloff, James R. P.
Contemporary social cognitive theories of aggression, such as the general aggression model (GAM), highlight the role of several key knowledge structures in aggressive behavior. There has been limited investigation of these structures in offender populations, however, meaning that their relevance to the rehabilitation of violent offenders cannot be adequately determined. In the present study, the role of three aggression-related knowledge structures—normative beliefs, behavioral scripts, and early maladaptive schema—along with trait anger, were examined with respect to the aggressive behavior of an offender sample. Normative beliefs and scripts were associated with aggression over and above the effect of anger, with these variables accounting for almost a quarter of the variance in participants' aggression. These findings suggest that the knowledge structures described by the GAM concurrently increase aggression and underscore the need for more routine and systematic targeting of aggression-related cognitions in violent offenders.